Brand awareness of Feel Iceland and its product range - Stefán Broddi Sigvaldason 1999- (2021)
Brand awareness is the degree to which consumers and prospective consumers are conscious of a company’s business and products. Brand image is the ideas and feelings that a consumer has towards the brand. Brands with high brand awareness and image reap the benefits of repeat purchases from consumers, and thus, gain competitive advantage. This research measured the extent to which consumers associate Feel Iceland’s products with the brand Feel Iceland, and thereby, Feel Iceland’s brand awareness. This was performed by analyzing if there is a deviation within the product range of Feel Iceland, or between COLLAB and the collagen supplement products, with respect to whether consumers associated them with Feel Iceland or not, and also to what extent. A survey questionnaire was conducted and distributed on social media to achieve a variety of responses, which totalled in at 252, as well as e-mail communication with the project manager at Feel Iceland. The results showed that there was a deviation in association between the products, where respondents associated the collagen supplements more with Feel Iceland than they associated COLLAB with Feel Iceland. Nonetheless, brand awareness was low for both products and is something that Feel Iceland can be recommended to improve.